1995
DOI: 10.1002/ana.410380308
|View full text |Cite
|
Sign up to set email alerts
|

The subacute levodopa test for evaluating long‐duration response in parkinson's disease

Abstract: The clinical relevance of a long-duration response (LDR) to levodopa therapy in Parkinson's disease (PD) has not been widely recognized. In 25 patients with moderate PD, we measured LDR on motor function after short periods of treatment with levodopa (subacute tests). Each subacute test lasted 15 days and consisted of the oral administration of levodopa at various interdose intervals (IDIs) of 48, 24, 12, 8, 6, and 5 hours. The goal for a subacute test was to achieve a satisfactory antiparkinsonian effect befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 18 publications
1
89
1
2
Order By: Relevance
“…The improvement produced by the LDR was larger than the improvement produced by the SDR. This observation is in accord with observations of Quattrone and colleagues [8] that the LDR is a large portion of the response to levodopa during repetitive dosing. The LDR is not a prolonged SDR, because a clearly defined SDR superimposed on the LDR could be seen in many of the subjects.…”
Section: Initial Response To Levodopasupporting
confidence: 92%
“…The improvement produced by the LDR was larger than the improvement produced by the SDR. This observation is in accord with observations of Quattrone and colleagues [8] that the LDR is a large portion of the response to levodopa during repetitive dosing. The LDR is not a prolonged SDR, because a clearly defined SDR superimposed on the LDR could be seen in many of the subjects.…”
Section: Initial Response To Levodopasupporting
confidence: 92%
“…However, our estimate of LDR amplitude corresponds to those estimates reported in earlier phases of the disease, from one third of the total levodopa response (disability progression after drug withdrawal), 6 to more than 100% of the SDR by using tapping speed recordings. 20,21 Our results suggest that the LDR persists and is still of significant magnitude after a mean disease duration of more than 15 years in STN-DBS-treated patients with PD who do not require medication after surgery. This extends previous observations with no reduction in LDR magnitude during a 4-year period 8 and with similar LDR magnitude after 8 years of PD progression.…”
Section: Commentmentioning
confidence: 89%
“…In addition, a beneficial effect of entacapone administration attenuating levodopa or DA agonist-induced dyskinesias in 6-OHDA-lesioned rats (Marin et al 2006) and in MPTP-treated monkeys (Smith et al 2003, Zubair et al 2007) has been already shown. Because it has been associated with levodopa, a presynaptic mechanism has been considered as one of the mechanisms involved in the LDR (Quattrone et al 1995;Nutt and Holford 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The SDR is the basis for the clinical phenomenon of the motor fluctuation known as "wearing-off". However, the LDR is a sustained motor improvement that takes days to build up and lasts for many hours to days after levodopa discontinuation (Nutt et al 1995;Quattrone et al 1995;Zappia et al 1997). A study in the novo patients (the ELLDOPA trial) has shown that the LDR may actually last for several weeks after cessation of levodopa treatment (Parkinson Study Group 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%